CROSSWALKING AS A TOOL TO DECIDE ARABIC LANGUAGE STANDARD IN MADRASA TSANAWIYAH: FROM ARABIC CURRICULUM TO ACTFL AND CEFR - Hidayah, Fathi (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
So far, Arabic language learning in Indonesia still uses national standards in the form of a curriculum. As a country that carries out intensive Arabic language learning from primary to postgraduate education levels, of course there must be adjustments to Arabic language learning standards with international language standards so that the learning carried out can compete and be recognized internationally. One way to adapt existing learning standards to international language learning standards is through the crosswalking technique. This research aims to provide a description of the procedures for crosswalking in Arabic language learning standards at the Madrasa Tsanawiya level. This research is a literature research design with data sources in the form of Arabic language learning standards in the madrasah tsanawiyah curriculum and international language standards ACTFL and CEFR. Next, data analysis uses the crosswalking technique. The results of the research show that the standard of Arabic language learning at the Madrasa Tsanawiya level in Indonesia is at novice low - intermediate high level for ACTFL standards and at level A1 - B2 for CEFR standards.